Low blood levels of the lncRNA MRPL20-AS1 are associated with severe obstructive sleep apnea. (3rd October 2022) - Zietzer, A; Nachtsheim, L; Duesing, P; Von Krosigk, M; Hosen, M R; Breitrueck, N; Goody, P R; Klussmann, J P; Nickenig, G; Jansen, F; Jansen, S
Abstract: Introduction: Obstructive sleep apnea syndrome (OSAS) is the most common sleep disorder and it is associated with arterial hypertension, heart failure, coronary artery disease as well as atrial fibrillation. The underlying pathomechanisms for this association are only incompletely understood. In recent years long non-coding RNAs (lncRNA) have been shown to be involved in various cardiovascular pathologies. The aim of this study is to identify lncRNAs which are associated with OSAS in order to provide potential therapeutic targets. Methods and results: In order to tackle this issue, we included 23 Patients with a suspected OSAS in a pilot study and sampled blood on the evening before and on the morning after polysomnographic analysis. Citrate was used to inhibit clotting of the blood and cellular components were removed by centrifugation, before the plasma was stored at −80°C. One patient had no sign of OSAS as indicated by an Apnea/Hypopnea-Index (AHI) <5 per hour and was therefore excluded. The remaining 22 patients had a mean age of 44.45 years and a mean AHI of 28.38 per hour. Three of the patients were female and nineteen were male. In four of those patients with high AHI levels, we performed a RNA sequencing analysis from the citrate plasma and found MRPL20-AS1 to be the most significantly regulated lncRNA after the night of polysomnographic analysis (A). Low coding potential of MRPL20-AS1 was confirmed in silico via the Coding-Potential Assessment Tool (http://lilab.research.bcm.edu/ ) resulting in a coding probability of 0.06148. Then MRPL20-AS1 levels were measured via qPCR in the remaining patients. From 19 patients, we obtained evaluable results. We found that MRPL20-AS1 blood levels had the tendency to be lower after the night of polysomnographic assessment (B). Interestingly MRPL20-AS1 levels were inversely correlated with the AHI of the OSAS patients (C). This indicates that severe OSAS was associated with low levels of MRPL20-AS1 in our cohort (D). In order to further investigate these results in vitro, we subjected human coronary artery endothelial cells (HCAECs) to hypoxia (1% and 5% O2) for 24 h. We found that hypoxia leads to a significant downregulation of MRPL20-AS1 in HCAECs (E). Conclusion: MRPL20-AS1 blood levels are lower in patients with severe OSAS after nocturnal hypoxia. In endothelial cells MRPL20-AS1 is downregulated after hypoxia. MRPL20-AS1 can therefore be useful to identify patients suffering from severe OSAS. Further investigations are needed to elucidate the biological function of MRPL20-AS1 in the context of OSAS and to investigate MRPL20-AS1 as a potential therapeutic target to counteract cardiovascular effects of OSAS Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Unviversity of BonnUniversity of Cologne